Analisis Pengendalian Persediaan Bahan Baku Dengan Metode Eoq ( Economic Order Quantity ) Pada Pt. Inti Kiat Alam - Hendrawati Hendrawati (Fakultas Ekonomi Universitas Borobudur, 2017)
Supplies a great effect on the cost aspects of a company. If a company has too much inventory it will be very detrimental because it requires huge investment costs, but the lack of supplies also will have an impact on the production process, so it can be detrimental to the company. This research was conducted at PT. IntiKiatAlam. PT. IntiKiatAlam is a company engaged in the field of herbal medicine. The focus of this research is only in analisisi raw material inventory control method EOQ (Economic Order Quantity).This study using Economic Order Quantity (EOQ) to determine the optimal amount of inventory. With this method it can be known how many orders are fixed and when to book return and maximum inventory. This study uses data Wenny honey inventories of raw materials in 2014. The calculation of the total cost of inventory before EOQ, - and based on the results of inventory planning with EOQ method, the application method EOQ, PT. IntiKiatAlam tips to optimize the amount of inventory, the total cost and the production process. Keywords: Economic Order Quantity, inventory, production processes.